Analysis of the vector tetraquark states with P-waves between the diquarks and antidiquarks via the QCD sum rules - Zhi-Gang Wang (European Physical Journal C: Particles and Fields, 2019)
Abstract In this article, we introduce a P-wave between the diquark and antidiquark explicitly to construct the vector tetraquark currents, and study the vector tetraquark states with the QCD sum rules systematically, and obtain the lowest vector tetraquark masses up to now. The present predictions support assigning the Y(4220 / 4260), Y(4320 / 4360), Y(4390) and Z(4250) to be the vector tetraquark states with a relative P-wave between the diquark and antidiquark pair.